Efektivitas Penggunaan Teknologi Informasi dalam Pengetahuan Masyarakat Adat Terhadap Praktik Konservasi Lingkungan di Provinsi Kalimantan Tengah - Richardus Indra Gunawan; Ganesha G (Multimatrix, 2021)
Indonesia has a dominant policy regarding deforestation, especially if it deals with large plantations, the mining sector, transmigration sites, construction of public facilities such as roads, reservoirs, urban forests, and so on. Meanwhile, land degradation caused by various activities that violate the law in the community as a result of policies that have not been right to be able to improve the welfare of its people. The Indonesian Government's policy in the form of the Million-hectare Peatland Project (PLG) in Central Kalimantan is one of the concrete examples of policies that sustainably lead to deforestation and land degradation. This is due to among them lack of planning that does not consider the carrying capacity of the environment, the culture of the local community, and local wisdom. As a result, when the land needs to be restored it will require high costs and much more time.The Government of the Republic of Indonesia took the initiative to conduct an intervention policy by making environmental management regulations specifically in the forestry sector. This policy includes the ongoing environmental conservation program from a decade ago to the present. Where the Government of the Republic of Indonesia at that time chose the Province of Central Kalimantan as a pilot province as the first Province that runs REDD+ regulations in Indonesia. In its implementation, an in-depth study of the effectivity level of information technology to measure the knowledge of indigenous peoples in Central Kalimantan Province is needed during the implementation of this conservation program. The aim of the study is to ensure that the conservation program is suitable for the conditions of indigenous peoples in Central Kalimantan Province. The results showed that indigenous peoples in Central Kalimantan Province did not yet have a proper understanding of conservation programs. This low level of knowledge of indigenous peoples has an impact on the level of participation of them in government programs, especially regarding environmental conservation. Meanwhile, indigenous peoples who already know about conservation programs, show that information about conservation programs can be obtained from Non-Governmental Organizations (NGOs) who are constantly visiting and providing information and assistance in the form of knowledge transfer to the community about conservation environment.Key Word: Conservation, Environment, Knowledge, Information Technology, Indigenous People, Central Kalimantan Province